Inspection of four advanced constitutive models for fine-grained soils under monotonic and cyclic loading - Duque, J.; Tafili, M.; Seidalinov, G.; Mašín, D.; Fuentes, W. (Acta geotechnica, 2022)
A wide range of geotechnical structures founded in fine-grained soils are subjected to complex cyclic loading scenarios. The prediction of their behavior has motivated the development of several constitutive models for soils under different mathematical frameworks. Some success has been achieved under certain simplified cyclic conditions. However, the performance of the models is usually not satisfactory when dealing with a wide range of test conditions, such as variation of the loading amplitudes, initial effective stresses, initial stress ratios, overconsolidation ratios, direction of the loading with respect to the bedding plane, among others. Even though this issue is well-known by model developers, few efforts have been made in the literature to analyze and discuss this and other models’ limitations. This article investigates the strengths and weaknesses of four advanced constitutive models for anisotropic fine-grained soils, namely: the anisotropic hypoplastic model by Fuentes et al. (Géotechnique 71(8):657–673, 2021), the SANICLAY-B elasto-plastic model by Seidalinov and Taiebat (Int J Numer Anal Meth Geomech 38(7):702–724, 2014), the constitutive Anamnesis model by Tafili (PhD thesis, Institute of Soil Mechanics and Rock Mechanics, Karlsruhe Institute of Technology, 2019) and the three surface kinematic hardening model proposed by Stallebrass and Taylor (Géotechnique 47(2):235–253, 1997) with transverse isotropic elasticity. In order to achieve that, simulation results with the models are qualitatively and quantitatively compared against a large number of experimental results under monotonic and cyclic loading on an anisotropic kaolin reported by Wichtmann and Triantafyllidis (Acta Geotech 13(5):1103–1128, 2018).